Hidden - Frost, Helen, 1949- (Square Fish, 2015)
When fourteen-year-olds Wren and Darra meet at a Michigan summer camp, both are overwhelmed by memories from six years earlier when Darra's father stole a car, unaware that Wren was hiding in the back.